Connectivity Correlates of Anxiety Symptoms in Drug‐Naive Parkinson's Disease Patients. Issue 1 (10th November 2020) - De Micco, Rosa; Satolli, Sara; Siciliano, Mattia; Di Nardo, Federica; Caiazzo, Giuseppina; Russo, Antonio; Giordano, Alfonso; Esposito, Fabrizio; Tedeschi, Gioacchino; Tessitore, Alessandro
Abstract: Background: Anxiety symptoms are common in Parkinson's disease (PD). A link between anxiety and cognitive impairment in PD has been demonstrated. Objectives: Using resting‐state functional magnetic resonance imaging, we investigated intrinsic brain network connectivity correlates of anxiety symptoms in a cohort of drug‐naive, cognitively unimpaired patients with PD. Methods: The intrinsic functional brain connectivity of 25 drug‐naive, cognitively unimpaired PD patients with anxiety, 25 without anxiety, and 20 matched healthy controls was compared. All patients underwent a detailed behavioral and neuropsychological evaluation. Anxiety presence and severity were assessed using the Parkinson's Disease Anxiety Scale. Single‐subject and group‐level independent component analyses were used to investigate functional connectivity differences within and between the major resting‐state networks. Results: Decreased connectivity within the default‐mode and sensorimotor networks (SMN), increased connectivity within the executive‐control network (ECN), and divergent connectivity measures within salience and frontoparietal networks (SN and FPN) were detected in PD patients with anxiety compared with those without anxiety. Moreover, patients with anxiety showed a disrupted inter‐network connectivity between SN and SMN, ECN, and FPN. Anxiety severity was correlated with functional abnormalities within these networks. Conclusions: Our findings demonstrated that an abnormal intrinsic connectivity within and between the most reported large‐scale networks may represent a potential neural correlate of anxiety symptoms in drug‐naive PD patients even in the absence of clinically relevant cognitive impairment. We hypothesize that these specific cognitive and limbic network architecture changes may represent a potential biomarker of treatment response in clinical trials. © 2020 International Parkinson and Movement Disorder Society Abstract :